LAW ENFORCEMENT AGAINST SHIP SHIPPING WHICH IS NOT SEAWORTHY AT CIREBON PORT - Farahdita, Naura; Sanusi, Sanusi; Nurhaqi , Ari (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
An important requirement is a Sailing Approval Letter (SPB) as a condition in seaworthy shipping or whether or not a ship can sail. Ships that are incomplete or absent the letter have violated the law or can be said to be a criminal offense in the shipping sector; the problem is how to enforce the law against ships that are not seaworthy and what the obstacles are at Cirebon II Port. The method used is an empirical juridical approach, looking at the law applicable in the community and people's behavior, especially in the field of shipping, in accordance with existing rules. This type of qualitative research, analytical descriptive, looks at the facts in the field. Data is taken from in-depth interviews with relevant stakeholders. This study found that law enforcement was not optimal because only the ship was detained while the captain and ship owner were not. The obstacle was due to PPNS's limited personnel; the captain fled, and the ship was unknown to its owner. PPNS in enforcing shipping laws must be sufficient, and the infrastructure facilities must be fulfilled; in addition, data collection on shipping ship owners and strict sanctions are needed for skippers and shipping ship owners.